Perancangan Arsitektur Enterprise Dalam Pengembangan SIMRS Bidang Pelayanan Penunjang Menggunakan TOGAF ADM (Studi Kasus: Rumah Sakit XYZ) - Rasyid Ramadhani Dharmawan; Luthfi Ramadani; Falahah Falahah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
To improve services to the community in the form of providing health services, both curative and rehabilitative, XYZ Hospitals require a Hospital Information System (HIS) to improve the efficiency and effectiveness of hospital operations. HIS aims to implement a policy of simplifying the bureaucracy to create a more proportional, effective, and efficient organization to improve the performance of the implementation of the Ministry of Health's duties as stated in the Minister of Health Regulation Number 25 of 2020 concerning Organization and Work Procedures of the Ministry of Health. HIS Developing requires a design called Enterprise Architecture (EA). EA can make it easier for hospitals to make business strategic plans and design a system that is integrated to make the organization's business processes more efficient. The limitation of the journal on the design of this EA is in the Support Service Field for XYZ Hospital. The EA design is carried out using references from the HIS Minister of Health Regulation, XYZ Hospital Strategic Plans, and the EA Framework, namely TOGAF ADM. This EA design produces an enterprise architecture at the Regional General Hospital which is expected to be a reference in developing information systems to improve health services to the community.